2008
DOI: 10.1016/j.neuron.2008.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Electrophysiological Indices of Negative Affect Predict Cocaine Self-Administration

Abstract: The motivation to seek cocaine comes in part from a dysregulation of reward processing manifested in dysphoria, or affective withdrawal. Learning is a critical aspect of drug abuse; however, it remains unclear whether drug-associated cues can elicit the emotional withdrawal symptoms that promote cocaine use. Here we report that a cocaine-associated taste cue elicited a conditioned aversive state that was behaviorally and neurophysiologically quantifiable and predicted subsequent cocaine self-administration beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
199
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(218 citation statements)
references
References 84 publications
18
199
0
1
Order By: Relevance
“…Interestingly, this AMPH experience also induced a significant up-regulation of AH-V1aR expression, similarly, as observed in pair-bonded males. While it is not surprising that drugs of abuse act on the same neurobiological substrates mediating natural reward (45)(46)(47)(48), our findings provide additional evidence to support the above notion and highlights the role of the neuropeptide AVP underlying naturally induced and drugfacilitated female-directed aggression in male prairie voles. These data also indicate the utility of the prairie vole model for evaluation of the effects of drug abuse on neural systems controlling adaptive forms of social behavior, such as mate guarding.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, this AMPH experience also induced a significant up-regulation of AH-V1aR expression, similarly, as observed in pair-bonded males. While it is not surprising that drugs of abuse act on the same neurobiological substrates mediating natural reward (45)(46)(47)(48), our findings provide additional evidence to support the above notion and highlights the role of the neuropeptide AVP underlying naturally induced and drugfacilitated female-directed aggression in male prairie voles. These data also indicate the utility of the prairie vole model for evaluation of the effects of drug abuse on neural systems controlling adaptive forms of social behavior, such as mate guarding.…”
Section: Discussionsupporting
confidence: 70%
“…This association has been attributed to a major mechanism of relapse in such individuals related to a dysphoric response to drug cue exposure (Koob, 2008;Wheeler et al, 2008). Similar to the findings for smokers (Drobes et al, 2006), there was a strong observed correlation between individual variation in attentional bias effects for drug cue and negative affect stimuli for cocaine-dependent individuals.…”
Section: Discussionsupporting
confidence: 67%
“…Both the middle cingulate and lateral orbital frontal cortex nodes within this network are functionally related to the emotional processing and regulation of aversive states (Singer et al, 2004). The observed increased functional connectivity within this network with increasing attentional bias effect for cocaine cues supports the concept of negative affective responses to drug cue exposure as a precipitant of relapse to drug seeking and use behavior via negative reinforcement mechanisms (Wheeler et al, 2008;Koob, 2009). Whether this association is because of a direct negative affective response to drug cues or reflects a response to conflict between drug craving and drug unavailability in the MRI setting is not known.…”
Section: Discussionmentioning
confidence: 55%
“…In general, these substances are readily consumed by mice and rats and elicit appetitive orofacial reactions if infused intraorally, suggesting a positive hedonic evaluation [28,29]. Moreover, mice and rats show increased dopamine efflux and dopamine release in response to free consumption or intraoral delivery of nonnutritive sweeteners [22,30,31].…”
Section: Artificial Sweetenersmentioning
confidence: 99%